2018
DOI: 10.1111/gcb.14097
|View full text |Cite
|
Sign up to set email alerts
|

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest

Abstract: Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far-red sun-induced chlorophyll fluorescence (SIF) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even-aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 107 publications
5
26
0
Order By: Relevance
“…However, F685 radiances (and/or F685 yields) provided a more reliable indicator of stand age, canopy chemistry, and physiological status than F740 radiances (or F740 yields), and was stable over older aged, closed canopy stands. This conclusion was also reached in a sister study for this campaign [34]. However, F685 radiances were non-linearly affected by the forest temperature difference (canopy-air, °C) throughout the diurnal cycle.…”
Section: Fluorescence and The Canopy-air Temperature Differencesupporting
confidence: 76%
See 2 more Smart Citations
“…However, F685 radiances (and/or F685 yields) provided a more reliable indicator of stand age, canopy chemistry, and physiological status than F740 radiances (or F740 yields), and was stable over older aged, closed canopy stands. This conclusion was also reached in a sister study for this campaign [34]. However, F685 radiances were non-linearly affected by the forest temperature difference (canopy-air, °C) throughout the diurnal cycle.…”
Section: Fluorescence and The Canopy-air Temperature Differencesupporting
confidence: 76%
“…This expectation was realized, since the CHM structure parameter for canopy height derived from LiDAR returns was strongly related to LP stand age (r 2 = 0.95, 2-33 years old in 2013), and was non-linearly related to F685 radiances (Figure 8). That particular finding was further studied in a separate analysis reported from this campaign [34] that capitalized on the inherent design of this site, based on the chronosequence of age classes. That study attributed the decline in F685 radiances and F685 yields across LP age classes to developmental processes that reduce hydraulic conductance in older trees [71,72], which would certainly affect the physiological performance we identified.…”
Section: Lidar Variablesmentioning
confidence: 98%
See 1 more Smart Citation
“…Particularly, the measurement of emitted Sun-Induced Fluorescence (SIF) is an emerging research field with growing interest. SIF is considered the most direct measurement of photosynthesis and facilitates the assessment of vegetation functioning [15,16]. Substantial progress has been made to assess the information content of SIF and its relation to plant photosynthesis across scales.…”
Section: Introductionmentioning
confidence: 99%
“…Data acquisition took place during the SWAMP (Spectrometry of a Wetland and Modelling of Photosynthesis) airborne campaign held on 11 July 2015 in Poland (the first HyPlant campaign taken over heterogeneous peatlands and surrounding ecosystems organized under the FLuorescence Explorer (FLEX) project supported by the European Space Agency (ESA)). Previous studies using HyPlant data have already revealed highly interesting insight into the information content of SIF and the functioning of ecosystems, mainly homogenous ones like croplands, grasslands, and forest areas [16,28,[36][37][38]. Rossini et al [37] measured the red and far-red SIF values with HyPlant over grass carpets treated with herbicides to estimate the rate of photosynthesis (P) and relationships between SIF and P. Wieneke et al [28] used the HyPlant-based SIF retrievals over sugar beet fields in the Rur river catchment to estimate GPP.…”
Section: Introductionmentioning
confidence: 99%